THE METHODOLOGY OF THE FINANCIAL PROVIDING OF ACTIVITY OF THE FEDERAL GOVERNMENT BUDGETARY INSTITUTIONS - R. Murav’Ev (Вестник университета)
In this article considered the key principles of financing federal state budgetary institutions, analyzed the main sources of financial support activities, and also the analysis of the structure of financial security of the federal government budgetary institutions.